(untitled) (Microbes and Health, 2014)
Naturally diseased climbing perch Anabas testudineus was confirmed to be caused by Aeromonas hydrophila bacteria by aeromonas isolation medium (AIM), 0/129 vibriostatic agent and esculin hydrolysis. Such naturally diseased koi fish weretreated with four antibiotics: captor (chlortetracycline hydrochloride BP 45%), renamox 15% -Vet (amoxicillin trihydrate BP), oxy-Dox-F (oxytetracycline 20% and + doxycycline 10%), renaquine 20% -Vet (flumequine) at lower, recommended and higher doses were performed to examine the efficacy of the drugs. Captor was given at doses of 0.8, 1.0 and 1.2 g/3 litres of water separately. Doses of renamox 15% -Vet were given at 0.8, 1.0 and 1.2 g/litre of water. Doses of oxy-Dox-F were 0.8, 1.0 and 1.5 g/Kg body weight and doses of renaquine were 10, 12, and 15 mg/Kg body weight. Among the four antibiotics, effect of captor and renaquine at recommended dose showed the best result where 100% fish were recovered. However, renamox and oxy-Dox-F showed best result at higher dose. DOI: http://dx.doi.org/10.3329/mh.v3i1.19770 Microbes and Health, June 2014. 3(1): 7-8